PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN TERUMBU KARANG DI PULAU SARANG KOTA BATAM - Armilus Armilus (Program Pascasarjana Universitas Riau, 2013)
Observation of community perception and participation in coral reef management werecarried out in Sarang Island to see the correlation between the community perception and participation with the coral reef management in Batam, from May to June 2012. The community perception (X1) is the highest (2.80) which the community perception of the coralreef condition is good and the community participation (X2) has the average 1.65, whichmeans that the community participation in the coral reef management is low and the government participation (X3) has the average 1.51 which means that the government participation in the coral reef management is very low. By using spearman rho correlation istoud the effect among variabels is highest and to know the correlation direction. than 0.05,there is a strong effect of the correlation; in contrast, if the correlation is smaller than 0.05,the effects among the variabels are weak. The score of community perception (X1) on the coral reef condition (Y) is r = 0.079 at level of significance of 0.05. It means that thecommunity perception (X1) of the coral reef has no strong effect of correlation (0.079 <0.05). The value of the community participation (X2) is r = 0.630 at level 0.05. Of the coralreef management (Y) had a significant effect of the coral reef condition (0.630 > 0.05). Thecorrelation between the community participation (X2) and the coral reef condition (Y) ispositive, which means that the lower the community participation in the coral reefmanagement, lower the coral reef condition will tend to. The correlation value of thegovernment participation (X3) is r = 0.604f at level 0.05, which means that the governmentparticipation (X3) had a significant effect on the coral reef management (0.604 > 0.5).